Pluralism and Ethnic and Sectarian Diversity in the Arab World: 12-16 Jumada al Akhir/26-30 November 1993 International Institute of Islamic Thought Herndon, Virginia (American Journal of Islam and Society, 1994)
lbis seminar, sponsored jointly by the International Institute of IslamicThought and the Waqf Fund of the Kuwaiti Ministry of Awqaf, washeld at Herndon, Virginia. Twenty-five papers were presented during theseminar's eight sessions, which were attended by scores of Arab Muslimscholars and intellectuals from the United States and abroad, either as primaryauthors of research papers, commentators, or contributors to theserious and in-depth debate that followed each session.Issues of democratization and how to deal with ethnic and sectariandiversity in a context of modem society have become topical and centralto the political and intellectual debates in the Arab world. During the pastfew decades, social and political instability has nndermined profoundlythe prospects for progress and prosperity in the Arab world. Pertinent tothis instability was the failure to establish consensual policies and institutionsin the post-Ottoman era. Hence, questions relating to "traditional"and "modem," "pan-Islamic" and "nationalist," "absolute" and "relative,"and "us" and "others" were raised prominently and discussed during theseminar's five days.The opening session, chaired by Hisham Altalib (IIIT), consisted ofthree contributions. The first was that of Khalid al Zir (Kuwaiti Ministryof Awqaf), who foc.ussed on the value of research as a higher value andemphasized the role of waqf in Islamic life. Taha J. al 'Alwani (President,lllT), spoke on behalf of IIIT and elaborated on the significance of ...